FEAR OF INCESTUOUS OIDA-POUS: UNEQUAL DISCOURSES AND TRAGEDY IN OEDIPUS THE KING - Suharjanto, Lucianus (International Journal of Humanity Studies (IJHS), 2024)
This research aims to explain the enigmatic fact in Sophocles Oedipus the King, where the discovery of regicide and origin coincides with the tragedy of patricide and incest in Oedipus. To achieve this, the research explores the unequal discourses of language and knowledge that result from the new awareness of the contingency of language. This research concludes with three discoveries through a forensic study of the discrepancies between the syntax in the text and the pistm of the dramatic character. First, the tension between the fate of the dramatic character (Oedipus) and the domination of the author of the text (Sophocles) is the symptomatic appearance of the unequal discourses between language as correspondence and language as a tool. Second, Oedipus tragedy of patricide and incest was a semantic reality rather than a real-life event representing a divine register. Third, as seen in the interplay between the oracle, fate, and the tragic self-knowledge in Oedipus the King, this drama explicates the incestuous origin of knowledge and its tragic impact on the body. This study contributes to the many-have-done discussions and critics of Oedipus the King. This research demonstrates that a lack of awareness regarding unequal discourses can lead to tragic consequences.